2011
DOI: 10.2473/journalofmmij.127.77
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Slurry Transport Database

Abstract: The transport conditions of solids in slurry pipelines cause the flow behavior of solid-liquid mixture to vary strongly and affect the hydraulic gradients in the systems. Since any transport design or correlation for slurry transport should be confirmed by a wide range of data, experiments in various flow regimes have been carried out over the years by different researchers.This study was, therefore, aimed at developing a slurry transport database for accumulation, input, editing, sorting, storing of the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For confirming the accuracy of evaluating hydraulic gradient of slurry flow with the analytical model, the experimental data (about 3000 points) in the database reported by Seitshiro et al [6] were compared with predicted values of i, as shown in Figure 8. It is recognised that the data scattering in a wide range of flow conditions could be found outside the ∓20% boundary (measured in the y-axis).…”
Section: Verification Of the Model With The Databasementioning
confidence: 99%
See 1 more Smart Citation
“…For confirming the accuracy of evaluating hydraulic gradient of slurry flow with the analytical model, the experimental data (about 3000 points) in the database reported by Seitshiro et al [6] were compared with predicted values of i, as shown in Figure 8. It is recognised that the data scattering in a wide range of flow conditions could be found outside the ∓20% boundary (measured in the y-axis).…”
Section: Verification Of the Model With The Databasementioning
confidence: 99%
“…Since most of the correlations were however derived at different flow regimes which depend on the mean velocity of the flow, the boundaries between the regimes should be determined whereas it is not easy to clearly distinguish one regime to another by observation. The objective of this paper is to demonstrate the applicability of an analytical model [5] to the settling slurry flow in horizontal pipes by using the Slurry Flow Database developed by Seitshiro et al [6] and to clarify the design procedure for the optimum operation condition. It is shown that both a condition factor indicating concentration profiles and a generalized particle Reynolds number are vital to predict the energy needed for transporting the slurry.…”
Section: Introductionmentioning
confidence: 99%